Role of Zakat in Poverty Reduction in Kelantan, Malaysia - Mohd. Ali, Ahmad Fahme (2011)
This study attempts to examine the effectiveness of monthly zakat distribution as a mechanism to poverty reduction in the state of Kelantan. The target population of this study is the fuqara and masakin categories of the Majlis Agama Islam Kelantan (MAIK) zakat recipients. Simple Random sampling procedure is applied to collect primary data related to zakat recipients from the poor and needy category of the ten districts of Kelantan. Poverty maps are derived based on the collected data. These facilitate an examination of the most affected area of poverty within the context of selected socio economic variables. The effects of zakat distribution on poverty are analyzed within the context of burden of poverty; specifically in terms of incidence, intensity and severity of poverty. These are examined using four major indices of poverty, which include the Headcount Index, Average Poverty Gap, Income Gap and Sen Index. The poverty incidence will be measured by using the headcount index that measures the ratio of people living below the poverty line compared to the total population. The Income Gap ratio and Poverty Gap Index will be used to measure the extent of poverty. These poverty measures give a more informative picture about how deep poverty is than the headcount index. It is obtained by multiplying the poverty headcount index by the ratio of the difference between the poverty line and the average income of the population living under the poverty line expressed as fraction of the poverty line. Finally, the Sen Index is used to measure the severity of poverty because it provides adequate information on the exact income distribution among the poor. Sen Index incorporates all the information on the number of poor, the extent of poverty short-fall per person and the income distribution among the poor as well. The analysis reveals that zakat distribution reduces poverty incidence, reduces the extent of poverty and lessens the severity of poverty. However, the current practice of zakat distribution in Kelantan only gives a small effect on increasing the income of the poor. Hence, by locating the perfect amount of zakat distribution to eliminate poverty and to offer alternative zakat distribution model is the best way in reducing the income inequality and maximization of social welfare. The best model of zakat distribution identified is based on had-kifayah. The above findings together with the identification of the group most affected by income inequality and poverty will pave the way towards policies for a more effective and efficient utilization of scarce zakat resources.